Potencial antifúngico de óleos-resina e extratos brutos hidroalcoólicos de Copaifera spp. frente a fungos filamentosos e leveduras - Andrade, Géssica (2015)
The increasing number of fungal infections has become a matter of great concern worldwide. The emergence of resistant strains is a particularly challenging issue. Species belonging to the genus Candida account for the wide occurrence of fungal infections in humans, especially vaginal and buccopharyngeal candidiasis. In addition, filamentous fungi can affect immunocompromised individuals and culminate in serious lung diseases. Plants are an important source of biologically active compounds and have played an important role in the search for new antifungal agents. In this context, copaiba stands out for its several medicinal properties. Aiming to develop new antimicrobials, in this work we have evaluated the in vitro antifungal action of the crude hydroalcoholic extract and oleoresin of several Copaifera species against filamentous fungi and yeasts by using the standard CLSI M27-A3 and M38- A2 methodology. The broth microdilution method aided determination of the Minimum Inhibitory Concentration (MIC) and the Minimum Fungicidal Concentration (CFM); it also helped to assess the antibiofilm activity and the synergistic action of the most promising samples. The C. duckei crude hydroalcoholic extract afforded the most promising result: MIC against C. albicans (ATCC 4939) and C. orthopsilosis (ATCC 96141) was 5.86 µg/mL. This extract exerted fungicide and fungistatic effects on C. albicans and C. orthopsilosis, respectively. As for the activity of the crude hydroalcoholic extracts of Copaifera spp. against yeasts, they provided antibiofilm Minimum Inhibitory Concentrations (CIMB50) ranging from 350 to >3000 µg/mL. Regarding the synergistic activity, almost none of the extracts acted synergistically with Amphotericin B. In conclusion, crude hydroalcoholic extracts obtained from the leaves of Copaifera spp. are promising sources of new antifungal agents and may become an alternative strategy to treat various infections.